Faktor Risiko Early Childhood Caries pada Anak UsiaPrasekolah di PAUD Kenanga 17 Kelurahan Penjaringan, Kecamatan Penjaringan, Jakarta Utara - Anita Rosa Delima; Setya Kusuma Arum (Lembaga Penelitian Universitas YARSI, 2015)
Dental caries is a multifactorial disease that can affect all levels of society. There are several factors that take part ini caries initiation. Caries risk factors in children are related to age, gender, use of bottles, tooth brushing frequency, the role of the mother, and parental education. The purpose of this studywas to find out factors related to the cause of early childhood caries experienced by preschool children at PAUD Kenanga 17 Kelurahan Penjaringan, Kecamatan Penjaringan, North Jakarta. An observational analytical methods with cross sectional approach was used in this study. Subject in this study consisted of 20 children as a total sample of the population. Data collection was carried out using questionnaires and def-t index was employed for dental examination. Data processing and statistical analysis using chi-square test were applied with a significance value of p less than 0.05. The results showed significant correlation between age (p value 0.001) and gander (p value 0.047) andearly childhood caries.hawever, no correlation was observed betwen the use of bottle (p value 0.909), frequency of tooth brushing (p value 1.00), role of mother (p value 1.00), and parental education (p value 0.798) and early childhood caries.